NUMERICAL METHODS WITH EXCEL - Tay Kim Gaik; Kek Sie Long; Rosmila Abdul Kahar (Penerbit UTHM, 2013)
Numerical Methods with Microsoft Excel® is written for engineering students who are studying Numerical Methods subject at undergraduate and postgraduate levels. This book offers several spreadsheet skills for students who have little knowledge of programming to implement tedious and repetitive calculations of Numerical Methods. Based on the authors’ teaching experiences in teaching university mathematics courses, this book provides many examples with a comprehensive step by step Excel® commands in solving numerical problems. We hope that this book is beneficial to all users, especially lecturers and students in teaching and learning Numerical Methods.